Achievement of competency in endoscopic sinus surgery of otolaryngology residents. (5th October 2013) - Laeeq, Kulsoom; Lin, Sandra Y.; Varela, David A. Diaz Voss; Lane, Andrew P.; Reh, Douglas; Bhatti, Nasir I.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis The goal of our study is to identify the number of Endoscopic Sinus Surgery (ESS) cases required to obtain competency in ESS, using a previously validated assessment tool. Study Design Prospective observational study. Methods Seventeen residents from Johns Hopkins Otolaryngology–Head & Neck Surgery residency program were evaluated as they performed endoscopic sinus surgery in the operating room. Global and checklist parts of the ESS instrument were used for assessment purposes. Items on the tool were grouped into three different milestones for analysis of data (Milestone 1 = Maxillary Antrostomy + Anterior Ethmoidectomy, Milestone 2 = Posterior Ethmoidectomy + Sphenoidostomy, Milestone 3 = Frontal Sinusotomy). Residents were deemed competent if they achieved a minimum score of 3 on a 5‐point Likert scale on each step of the surgery. Results A total of 73 evaluations were completed for 17 residents (Postgraduate Level 2–5) by eight evaluators between 2009 and 2011. A 60% probability of achieving competency in performance of all milestones of ESS is obtained with performing 42 ESS procedures and the probability is increased to a 100% with performance of 55 endoscopic sinus surgery procedures. On average it took residents 23 cases to become competent in performance of maxillary antrostomy and anterior ethmoidectomy. Conclusions Our results suggest that it requires 42 ESS procedures to attain a 60% probability of competency in ESS. These results have implications for otolaryngology residency programs when developing curriculum and benchmarks for the training residents. Laryngoscope, 123:2932–2934, 2013